The Economic Effects of the Tax Reform: Dynamic Input-output Model Approach - Hong, Cheng-Yih; Hsu, Chen-Jung; Li, Jian-Fa (International Journal of Economics and Financial Issues, 2018)
The financial crisis in 2008 severely damaged Taiwan’s economy, increased unemployment, and reduced the national income level, which has remained low ever since. These consequences have affected funding for various pension systems, particularly national pensions, and thus are of great concern to the government. The National Pension Act stipulated a 1% business tax increase to fund the national pension system. Hence, this study investigates the impact the act on economic growth and offers feasible suggestions for reform based on empirical evidence. Dynamic Input-Output models are designed to analyze the various positive and negative impacts on the economy. Empirical evidences suggests that Although raising business tax by 1% yields certain negative outcomes, proper use of transfer expenditure with financial flexibility yields more positive outcomes, manifested in the growth of NT 8.622 billion, 2.2 billion, and 2.256 billion in induced production, gross added value, and earned income, respectively, as well as the employment increase of 3,232 new workers. Finally, through the tax revenue model, transfer expenditure is estimated to yield an additional NT 5.4711 billion from business tax, personal income tax, and corporate income tax as a “fiscal dividend.” Keywords: Tax Reform, Dynamic Input-Output Model, Business Tax, Economic Effects JEL Classifications : C67, D57, E62, H20